Transformational Change for People and the Planet Evaluating Environment and Development - Uitto, Juha I.; Batra, Geeta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This Open Access book deals with the pressing question of how to achieve transformational change that reconciles development with environmental sustainability. It particularly focuses on the role of evaluation in finding sustainable solutions. Environment and development are closely interlinked, as are human health and ecosystem health. The pandemic that began in 2020 demonstrated in no uncertain terms how destruction of habitats has allowed hitherto unknown pathogens spill over to humans wreaking havoc on people$1 (Bs lives and livelihoods. We are already seeing the impacts of global climate change in terms of heatwaves, forest fires and increased storms. The Sustainable Development Goals (SDGs) explicitly recognize the equal importance of the social, economic and environmental dimensions of development. In these turbulent times, when humankind faces multiple complex challenges it is essential to know that our responses are effective and that they make a positive difference. Evaluationcan provide invaluable lessons to how we design policies, strategies and programs and how we allocate limited resources between competing priorities. This book brings together key thinkers and practitioners from the public and private sectors, from major multilateral organizations and from bilateral donor agencies, to present the latest knowledge and experience on how to evaluate interventions in the nexus of environment and development. The book does not promote any particular approach or methodology, but rather emphasizes the need for mixed methods to address the question at hand in the best and most suitable manner. It covers cases from a variety of fields, from climate change mitigation and adaptation, energy efficiency and renewable energy, natural resources management, biodiversity conservation and more. This book is not a conference proceedings although it has its roots in the Third International Conference on Evaluating Environment and Development organized by the GEF Independent Evaluation Office in October 2019. The conference brought together a larger number of established and upcoming evaluators, researchers and evaluation users from the Global North and South, representing a wide variety of organizations, to discuss the frontiers of environment and development evaluation. Following the conference, the editors identified and contacted the participants who made key contributions at the conference and asked them to develop their ideas and papers into book chapters according to a coherent plan.s
1. Introduction -- Section I: Transformational Change -- 2. Evaluation for Transformational Change: Learning From Practice -- 3. Transformational Change for Achieving Scale: Lessons for a Greener Recovery -- Section II: Drivers of Sustainability -- 4. Sustainability After Project Completion: Evidence from the GEF -- 5. From the Big Picture to Detailed Observation: The Case of GEF IEO$1 (Bs Strategic Country Cluster Evaluations -- 6. Staying Small and Beautiful: Enhancing Sustainability in the Small Island Developing States -- 7. Assessing Sustainable Development Interventions -- 8. Can We Assume Sustained Impact? Verifying the Sustainability of Climate Change Mitigation Results -- Section III: Evaluating Climate Change Mitigation and Adaptation -- 9. Using a Realist Framework to Overcome Evaluation Challenges in the Uncertain Landscape of Carbon Finance -- 10. Evaluation$1 (Bs Role in Development Projects: Boosting Energy-Efficiency in a Traditional Industry in Chad -- 11. EnablingSystems Innovation in Climate Change Adaptation: Exploring the Role for MEL -- 12. Assessing the Evaluability of Adaptation-focused Interventions: Lessons from the Adaptation Fund -- 13. Evaluating Transformational Adaptation in Smallholder Farming: Insights From an Evidence Review -- Section IV: Evaluation Approaches -- 14. Evaluation at the Endgame: Evaluating Sustainability and the SDGs by Moving Past Dominion and Institutional Capture -- 15. Importance and Utilization of Theory-based Evaluations in the Context of Sustainable Development and Social-Ecological Systems -- 16. Pathway to the Transformative Policy of Agenda 2030: Evaluation of Finland$1 (Bs Sustainable Development Policy -- 17. Evaluating for Resilient and Sustainable Livelihoods: Applying a Normative Framework to Emerging Realities -- 18. Measuring the Impact of Monitoring: How We Know Transparent Near-Real-Time Data Can Help Save the Forests -- 19. Application of Geospatial Methods in Evaluating Environmental Interventions and Related Socioeconomic Benefits.s
Keywords: Sustainability; Environment; Social sciences; Social policy; Public administration; Sustainability; Environmental Sciences; Society; Social Policy; Public Administration